Effects of Social Comparison, Travel Envy and Self-presentation on the Intention to Visit Tourist Destinations - Danielle Fernandes Costa Machado; Paula Cândida do Couto Santos; Mirna de Lima Medeiros (BBR: Brazilian Business Review)
Sharing travel experiences through social networks has become a very common practice today. Access and exposure to posted content can generate, in users, behavioral and emotional reactions capable of affecting their intention to travel. Based on this, the objective of the present work is to verify the effects of behavioral characteristics (social comparison, envy and self-presentation) on the intention to visit destinations, as displayed by users on social networks--more specifically, on Instagram. The study methodology consists of a survey applied online from May to June 2018 with Instagram users, in which we obtained 547 valid responses. For data analysis, we used descriptive statistics, factor analysis, and logistic regression to test and confirm the hypotheses of the presented theoretical model. The results indicate that envy and social comparison increase the odds of intention to visit a destination, with the strongest effect being related to the social comparison variable.